2010
DOI: 10.1089/lap.2008.0329
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pediatric Inguinal Hernia Repair: No Ligation, Just Resection

Abstract: No recurrences have been observed. We conclude that laparoscopic repair of CIH is feasible using this technique of complete resection of the processus vaginalis and surrounding parietal peritoneum. This series does not conclude on the need for the internal ring to be closed when found to be wider than 10 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 13 publications
1
30
1
2
Order By: Relevance
“…It is reported that to obtain a near-zero recurrence rate, it may be essential for the suture to enclose the hernia defect completely, independent of any division of the distal sac [6,10,12]. Recently, another laparoscopic hernia repair was introduced with a low recurrence rate, in which the hernia sac and the parietal peritoneum surrounding the internal inguinal ring were completely resected without a purse string suture if an internal ring was small [15]. This procedure allowed the peritoneal scar tissue to close the area of the ring.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that to obtain a near-zero recurrence rate, it may be essential for the suture to enclose the hernia defect completely, independent of any division of the distal sac [6,10,12]. Recently, another laparoscopic hernia repair was introduced with a low recurrence rate, in which the hernia sac and the parietal peritoneum surrounding the internal inguinal ring were completely resected without a purse string suture if an internal ring was small [15]. This procedure allowed the peritoneal scar tissue to close the area of the ring.…”
Section: Discussionmentioning
confidence: 99%
“…31 His series of 712 inguinal hernias repaired with a Z-stitch reported a recurrence rate of 2.6%. 32 Riquelme and colleagues 33 argue for an intracorporeal dissection and resection of the hernia sac with no ligation. This study of 71 patients argues that the scarring that occurs from sac dissection is all that is needed to close the defect.…”
Section: Intracorporeal Repairmentioning
confidence: 99%
“…Recurrence rates are statistically unaffected by not ligating the sacthe absence of adverse effects on herniorraphy without sac ligation in adults (7). A prospective study of laparoscopic inguinal hernia repair in children by Schier showed that there is no difference in suturing or not after the peritoneum was incised and the sac resected (8). Veena Kumari et al showed that closure of the hernial sac is not necessary in herniotomy associated with orchiopexy.…”
Section: Discussionmentioning
confidence: 99%